2012
DOI: 10.1098/rspb.2012.1477
|View full text |Cite
|
Sign up to set email alerts
|

Towards an integrated network of coral immune mechanisms

Abstract: Reef-building corals form bio-diverse marine ecosystems of high societal and economic value, but are in significant decline globally due, in part, to rapid climatic changes. As immunity is a predictor of coral disease and thermal stress susceptibility, a comprehensive understanding of this new field will likely provide a mechanistic explanation for ecological-scale trends in reef declines. Recently, several strides within coral immunology document defence mechanisms that are consistent with those of both inver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
145
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(148 citation statements)
references
References 95 publications
3
145
0
Order By: Relevance
“…In addition, this Hsp is also involved in the immune response, particularly interacting with the Toll-like receptor (TLR) signaling pathway (Pockley et al 2008, Quintana & Cohen 2011. In corals, many immune mechanisms for resisting infections and maintaining tissue integrity have been described, including TLRs, the melanin-synthesis pathway, a component of the prophenoloxidase pathway and antimicrobial and enzymatic activities (Geffen & Rosenberg 2005, Mydlarz & Harvell 2007, Palmer et al 2008, Dunn 2009, Mydlarz et al 2010, Palmer & Traylor-Knowles 2012, Libro et al 2013; however, few reports have examined the involvement of a Hsp in coral immune response to any coral disease , Brown et al 2013. In this context, transcriptional upregulation of the hsp70 gene in the coral A. millepora infected by Vibrio coralliilyticus has been proposed to be an element of the defense response of the coral, possibly by acti vating other components of the coral effector im mune systems, such as the prophenoloxidase cascade (Brown et al 2013).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, this Hsp is also involved in the immune response, particularly interacting with the Toll-like receptor (TLR) signaling pathway (Pockley et al 2008, Quintana & Cohen 2011. In corals, many immune mechanisms for resisting infections and maintaining tissue integrity have been described, including TLRs, the melanin-synthesis pathway, a component of the prophenoloxidase pathway and antimicrobial and enzymatic activities (Geffen & Rosenberg 2005, Mydlarz & Harvell 2007, Palmer et al 2008, Dunn 2009, Mydlarz et al 2010, Palmer & Traylor-Knowles 2012, Libro et al 2013; however, few reports have examined the involvement of a Hsp in coral immune response to any coral disease , Brown et al 2013. In this context, transcriptional upregulation of the hsp70 gene in the coral A. millepora infected by Vibrio coralliilyticus has been proposed to be an element of the defense response of the coral, possibly by acti vating other components of the coral effector im mune systems, such as the prophenoloxidase cascade (Brown et al 2013).…”
Section: Resultsmentioning
confidence: 99%
“…To be effective, we need to fully explore, and embrace, the intricacies and complexities of coral holobiont health 12 . This will require understanding the role of immunity in maintaining and degrading homeostasis, inclusive of mutualisms and under environmental change 13,14 .…”
Section: Immunity Purveyor Of Healthmentioning
confidence: 99%
“…In the last two decades, important efforts have focused on identifying microorganisms associated to coral diseases , as well as on determining the contribution of local and global environmental factors in the emergence of these diseases (Sokolow 2009). Yet, the mechanisms of immune response in corals are just beginning to be studied systematically (Palmer and Traylor-Knowles 2012). Genome and transcriptome analyses from various coral species, including the staghorn corals Acropora digitifera (Shinzato et al 2011), Acropora millepora (Miller et al 2007;Weiss et al 2013), and Acropora cervicornis (Libro et al 2013), the cauliflower coral Pocillopora damicornis (Vidal-Dupiol et al 2013), and the mountainous star coral Orbicella faveolata (previously Montastraea faveolata) (Schwarz et al 2008), have revealed the presence of a variety of conserved immune-type genes predicted to participate in the three functional compartments of any immune reaction, i.e., immune recognition, intracellular signaling, and effector response.…”
Section: Introductionmentioning
confidence: 99%